Penerapan Knowledge Management System Menggunankan Algoritma Levenshtein - Orissa Octaria; Ermatita Ermatita; Sukemi Sukemi (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2019)
Knowledge management (KM) is an important thing to store or possess existing knowledge. The difficulty of getting knowledge that has actually been known for a long time about special planning for new information is to repair a certain position, in this case the container that contains several private universities in Palembang. The lecturer can only find out how the system discusses in the college, and many other knowledge that must be discussed by the new lecturer. Therefore the Knowledge Management System (KMS) will be built using the Inukshuk Model to become a means for existing knowledge, while the algorithm for searching knowledge stored in KMS is the Levenshtein Algorithm. The selection of the Levenshtein algorithm itself which uses this algorithm measures the relationship between strings (words to words, words to sentences and sentences to sentences) by calculating the edit distance, so that it will produce a high level of acquisition. The result is a KMS that is important for private universities to store and manage knowledge web-based services to make it easier for today's users to use many internet networks.